Employment Opportunity as a Driver of Student Mobility - Farrugia, Christine (International Higher Education, 2016)
Taking data from the Institute of International Education’s Open Doors report, the theme of employment is analyzes in terms of student interest. Student interest in employment opportunities and how that affects mobility is analyzed.